2014
DOI: 10.1007/s10661-014-4168-9
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchal clustering yields insight into multidrug-resistant bacteria isolated from a cattle feedlot wastewater treatment system

Abstract: Forty-two percent of Escherichia coli and 58% of Enterococcus spp. isolated from cattle feedlot runoff and associated infiltration basin and constructed wetland treatment system were resistant to at least one antibiotic of clinical importance; a high level of multidrug resistance (22% of E. coli and 37% of Enterococcus spp.) was observed. Hierarchical clustering revealed a closely associated resistance cluster among drug-resistant E. coli isolates that included cephalosporins (ceftiofur, cefoxitin, and ceftria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
0
11
1
Order By: Relevance
“…The minor bacterial species, E. durans , is considered undesirable, even though no report has yet indicated any pathogenic effect of this bacterium on dairy cows. Previous studies have however shown its correlation with antibiotic gene transfer24. One possible mechanism of LAB additives in shaping the silage microbiota during the fermentation process was their ability in releasing antagonistic materials25.…”
Section: Discussionmentioning
confidence: 99%
“…The minor bacterial species, E. durans , is considered undesirable, even though no report has yet indicated any pathogenic effect of this bacterium on dairy cows. Previous studies have however shown its correlation with antibiotic gene transfer24. One possible mechanism of LAB additives in shaping the silage microbiota during the fermentation process was their ability in releasing antagonistic materials25.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 illustrates how IFAP can lead to adverse health effects in nearby communities via the generation and spread of microbial and chemical hazards. Studies have identified bacterial pathogens, such as antibiotic-resistant strains of Staphylococcus and Enterococcus, in and around IFAP operations, including colonizing animals and surfaces [7][8][9][10], in manure [11][12][13][14][15][16], and carried by flies [17,18] and rats [19] near operations. IFAP is also a source of airborne pathogens [8,[20][21][22], endotoxins [23], particulate matter (PM) [24], hydrogen sulfide (H 2 S), ammonia, odorous chemicals, and other contaminants [23,[25][26][27][28], which may be spread from operations to the downwind environment, e.g., via ventilation fans and emissions from decomposing manure [7,8,26,27,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, antibiotics have been detected in the ng L À1 to lg L À1 range in surface waters, where the possible bioaccumulation and the induction of drug resistance in bacteria may affect environmental http://dx.doi.org/10.1016/j.chemosphere.2015.04.102 0045-6535/Ó 2015 Elsevier Ltd. All rights reserved. and human safety (Corvaglia et al, 2008;Xu et al, 2011;Manzetti and Ghisi, 2014;Lee et al, 2014;Iliev et al, 2015;Jahne et al, 2015).…”
Section: Introductionmentioning
confidence: 99%